2019
DOI: 10.3897/folmed.61.e39425
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic approaches in locked-in syndrome

Abstract: Locked-in syndrome (LIS) is a neuropsychological condition, in which patients present with quadriplegia, lower cranial nerve paralysis, and mutism. Diagnosis of LIS is difficult because of the similarities with other related syndromes, but it is of crucial importance to establish precise and early diagnosis in order to make the appropriate decisions according to the intervention and treatment planning. Access to a multidisciplinary, specialized team provides opportunity for continued improvement.  In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 69 publications
0
12
0
1
Order By: Relevance
“…30 To avoid pulmonary complications, which are the main cause of death, chest physiotherapy like deep breathing exercises, frequent position changes, postural drainage and suctioning is recommended. 164 Diaphragmatic pacing, which is established for spinal cord injured patients, is also an option that showed benefits for a LiS patient already. 165 Although a systematic review found insufficient evidence for the benefits of physical exercise in physical recovery of LiS patients, a positive trend was seen for muscle strength, tone, walking ability and activities in daily living and the need for well-designed studies was stated.…”
Section: Treatmentmentioning
confidence: 99%
“…30 To avoid pulmonary complications, which are the main cause of death, chest physiotherapy like deep breathing exercises, frequent position changes, postural drainage and suctioning is recommended. 164 Diaphragmatic pacing, which is established for spinal cord injured patients, is also an option that showed benefits for a LiS patient already. 165 Although a systematic review found insufficient evidence for the benefits of physical exercise in physical recovery of LiS patients, a positive trend was seen for muscle strength, tone, walking ability and activities in daily living and the need for well-designed studies was stated.…”
Section: Treatmentmentioning
confidence: 99%
“…Patterson and Garbois described 139 patients with LIS; 82 had an infarction in the pons' base. The other patients had different etiologies, such as trauma, central pontine myelinolysis, tumors, encephalitis, neuro-Behcet's disease, multiple sclerosis, and other etiologies of less frequency [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…While consciousness is impaired, there has been a report of impaired attention, executive function, and memory [ 4 ]. Respiration is often impaired in these patients when the lateral tegmentum is involved [ 5 ]. Anarthria is due to paralysis of the facial-glosso-pharyngo-laryngeal muscles and damage of the corticobulbar fibers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations